Dynamics in gut microbiota diversity, composition, and assembly reveal the adaptability of invasive snail Pomacea canaliculata during hibernation in rice fields - Yao, Fucheng; Li, Chuang; Chen, Yingtong; Zhang, Jiaen; Shi, Zhaoji; Qin, Zhong (Frontiers in Microbiology, 2025)
The gut microbiota plays a crucial role in host immunity and metabolism and may facilitate the adaptation of invasive species to new environments. During hibernation, gut microbial communities undergo compositional shifts to help hosts cope with low temperatures and food scarcity. However, the dynamics of gut microbiota during hibernation in invasive animals remain poorly understood. Here, we conducted an in situ hibernation experiment on the invasive freshwater snail Pomacea canaliculata to investigate changes in its gut microbiota over the course of hibernation. Gut samples were collected at pre-hibernation (day 0) and on the 15th, 30th, 60th, 90th, and 120th days of hibernation, followed by 16S rRNA gene sequencing. Results showed that the survival rate of snails reached 85.7% after 120 days. The Shannon diversity index of gut microbiota increased with the duration of hibernation. Although species richness remained relatively stable, increased evenness led to higher alpha diversity. After 60 days of hibernation, the structure of gut microbial community changed. The dominant phylum shifted from Firmicutes to Bacteroidota (formerly Bacteroidetes) as hibernation progressed. Short chain fatty acids (SCFAs) producing genera such as Acetobacteroides, Bacteroides, Macellibacteroides, and Cetobacterium increased in abundance during hibernation, likely providing an energy source for both the gut and host. Gut microbiota changes appeared to be driven largely by stochastic assembly processes. Additionally, anaerobic bacteria and potential pathogens increased in abundance during hibernation. These adaptive shifts in gut microbiota may help maintain host metabolic and immune functions during hibernation and potentially contribute to the invasiveness of P. canaliculata.